THE ROLE OF EUPHEMISMS IN DOCTOR–PATIENT COMMUNICATION - Kurbanova Nargiza Abdisoatovna (International Journal of Literature and Language Studies, 2026)
Nowadays, the role of euphemistic language in doctor–patient communication has become one of the most important issues in medical rhetoric and deontology. Doctors and nurses often use soft and indirect expressions in order to reduce the emotional stress of patients and to create hope during treatment. In modern linguistics, much attention is paid to the study of rhetorical tools that influence human psychology and interpersonal communication. Euphemisms are among the most effective linguistic means in medical discourse because they help to soften frightening diagnoses, decrease anxiety, and establish trust between medical staff and patients. This article analyzes the use of euphemisms in the speech of doctors in English and Uzbek languages, their stylistic and psychological functions, and the importance of speech culture in medical communication. The article also highlights examples from real-life medical situations and literary discourse.